Soft pneumatic actuators for mimicking multi-axial femoropopliteal artery mechanobiology. (1st July 2022) - Fell, Cody; Brooks-Richards, Trent L; Woodruff, Maria A; Allenby, Mark C
Abstract: Tissue biomanufacturing aims to produce lab-grown stem cell grafts and biomimetic drug testing platforms but remains limited in its ability to recapitulate native tissue mechanics. The emerging field of soft robotics aims to emulate dynamic physiological locomotion, representing an ideal approach to recapitulate physiologically complex mechanical stimuli and enhance patient-specific tissue maturation. The kneecap's femoropopliteal artery (FPA) represents a highly flexible tissue across multiple axes during blood flow, walking, standing, and crouching positions, and these complex biomechanics are implicated in the FPA's frequent presentation of peripheral artery disease. We developed a soft pneumatically actuated (SPA) cell culture platform to investigate how patient-specific FPA mechanics affect lab-grown arterial tissues. Silicone hyperelastomers were screened for flexibility and biocompatibility, then additively manufactured into SPAs using a simulation-based design workflow to mimic normal and diseased FPA extensions in radial, angular, and longitudinal dimensions. SPA culture platforms were seeded with mesenchymal stem cells, connected to a pneumatic controller, and provided with 24 h multi-axial exercise schedules to demonstrate the effect of dynamic conditioning on cell alignment, collagen production, and muscle differentiation without additional growth factors. Soft robotic bioreactors are promising platforms for recapitulating patient-, disease-, and lifestyle-specific mechanobiology for understanding disease, treatment simulations, and lab-grown tissue grafts.